Involvement of local and non-local hunters in the tasks of the hunting club as exemplified by WKŁ 294 Hubertus in Bydgoszcz in the period of time before and during the COVID-19 pandemic - Codrow, Hubert; Graczyk, Radomir; Wierzbicka, Anna (Polish Journal of Natural Sciences, 2023)
In Poland, hunting can be practiced only by a member of the Polish Hunting Association (PZŁ) . Hunting club (basic unit of PZŁ) members include people residing on the club’s premises, as well as non-local hunters. An analysis of hunter involvement in the club’s tasks was carried out, on example of the Military Hunting Association no. 294 and covering hunting seasons from the 2018/2019 to the 2021/2022. The research was based on the data available in the PZŁ club system and the club’s documentation. Local hunters show greater interest and efficiency during individual hunts. Membership in more than one club does not reduce involvement in the club’s activities. Hunters prefer to pay the contribution for the development of the club rather than work it off. Local hunters engage in conducting the animal inventory. The impact of the COVID-19 social restrictions on the increase in hunting activity was ambiguous.